Influências de dietas ricas em ácidos graxos saturados e insaturados sobre o miocárdio de ratos - Pinotti, Matheus Fécchio [UNESP]; Silva, Maeli Dal-Pai [UNESP]; Sugizaki, Mário Mateus [UNESP]; Novelli, Yeda Santana Diniz [UNESP]; Sant'Ana, Lea Sílvia [UNESP]; Aragon, Flávio Ferrari [UNESP]; Padovani, Carlos Roberto [UNESP]; Novelli, Ethel Lourenzi Barbosa [UNESP]; Cicogna, Antonio Carlos [UNESP] (My University, 2007)
Objectives: To study the influence of saturated (SFA) and unsaturated fatty acid (UFA) rich diets on mechanical function, morphology and oxidative stress in rat myocardium. Methods: Male, 60-day-old Wistar rats were fed a control (n=8), a SFA (n=8), or a UFA-rich diet (n=8) for sixty days. Mechanical function was studied in isolated left ventricle papillary muscle under isometric and isotonic contractions, in basal conditions (1.25mM calcium chloride) and after 5.2mM calcium chloride and beta-adrenergic stimuli with 1.0μM isoproterenol. Left ventricle fragments were used to study oxidative stress and morphology under light and electron microscopy. Results: SFA and UFA-rich diets did not change myocardium mechanical function. Both diets caused oxidative stress, with high lipid hydroperoxide and low superoxide-dismutase concentrations. UFA rich diet decreased catalase expression and SFA rich diet decreased the amount of myocardial glutathione-peroxidase. Both diets promoted light ultrastructural injuries such as lipid deposits and cell membrane injuries. Conclusion: Results suggest that SFA and UFA rich diets do not alter isolated muscle mechanical function, but promote light myocardial morphological injuries and oxidative stress.
Influences of rich in saturated and unsaturated fatty acids diets in rat myocardium
Keywords: Diet; Fatty acids; Myocardium; Oxidative stress; Rats